The GFIT Scale: Measuring Goals Following Interpersonal Transgressions. Issue 2 (1st February 2018) - Rasmussen, Kyler R.; Boon, Susan D.
ABSTRACT: In two studies, we created and validated a scale assessing 12 possible goals that individuals might wish to pursue when transgressed against by another person (e.g., relationship maintenance, power over the offender, retributive justice). Results demonstrated that the 12 subscales of the Goals Following Interpersonal Transgressions scale (GFIT) were reliable and exhibited convergent and discriminant validity with transgression-related interpersonal motivations (i.e., the TRIM), and relevant personality traits (i.e., the Dark Triad). Additional analyses revealed that the structure of the scale was robust across different kinds of transgressions and for differing relationships between victim and offender. We argue that the GFIT is a versatile scale with several advantages over existing measures.